Strategi Peningkatan Kurikulum Pendidikan Islam Terpadu - saehudin saehudin; Acep Sutisna; Mimin Mintarsih (TA'DIB: Jurnal Pendidikan Agama Islam, 2023)
This study aims to illustrate how the effectiveness of an integrated Islamic values-based curriculum conducted at the Sukabumi City Hayatan Thayyibah Integrated Islamic Boarding School. This study uses a qualitative approach and qualitative descriptive methods. The data analysis technique starts from data collection, data reduction, data presentation and conclusion drawing. The results of this study indicate that: 1) The concept of an integrated curriculum developed in this school uses a correlated type of curriculum between the national curriculum (kurtilas) and the Islamic curriculum as the development of its Islamic values. 2) The implementation of an integrated curriculum carried out in this school is the integration of the national curriculum (kurtilas) towards the boarding curriculum with religious clusters whose references are taken from classical books, but in practice using separated subject curriculum with the development of character building programs as habituation of good character in the boarding school environment. 3) Integrated curriculum evaluation by involving the principal through continuous supervision of the implementation of curriculum development. 4) The supporting factors are good management and school facilities, the atmosphere of the pesantren-based school environment runs well. The inhibiting factor is the lack of communication between the school and parents, the structure of the school curriculum is fat because of the large number of subjects.